THE ATTRACTIVENESS OF CAREER DEVELOPMENT SYSTEMS; TO WHAT EXTENT DO THEY MOTIVATE CIVIL SERVICE EMPLOYEES IN ZIMBABWE. - Mabwe, Notion (IJRDO - Journal of Business Management, 2016)
Career development systems play a pivotal in the organisation development. Career development is viewed today as a kind of partnership with employees. It is also a key component of a company’s attraction and retention strategy. Many individuals will not consider employment with an organization unless it offers career development as a basic component of its culture. The current unfavorable economical situation in Zimbabwe is gradually driving away the prioritization of career development in many organizations especially civil service. It is deliberated that Zimbabwe has to seek for bigger competiveness in the entire continent and the world in general. However, the duty of civil service to create the environment benevolent for increasing competiveness is evidently lacking. The challenges associated with the changing nature of work and the workplace environment is a matter of life concern that requires a skilled, knowledgeable workforce with individuals who are adaptive, flexible, and focused on the future. Career development systems have a great influence on motivating employees in civil service. Today's employees are more career conscious than ever. They are demanding more in terms of personal growth and development. Organizations that fail to allow employees to meet their individual needs always perished. This paper analyzed the extent to which the attractiveness of career development system motivates civil service employees. The author explored in the Career Development systems that seek to match the needs of the employee with those of the organization with the great intention of motivation. It is however essential that organizations place a high value on Development systems career. This allows employees to fulfill their career needs, and organizations in future benefit by retaining a greater number of their competent and qualified employees.